Push and pull factors associated with the consumption of women’s professional basketball games: A canonical correlation analysis - Min, Sophia D.; Zhang, James J.; Byon, Kevin K. (Frontiers in Psychology, 2022)
The purpose of this study was to empirically investigate the interrelationships between push and pull factors associated with the consumption of women’s professional basketball games. Multiple factors pertaining to sport consumers’ internal needs, identified as “push” factors, contain various intangible socio-psychological motivations representing an individual’s intrinsic desires that drive consumers toward certain goal-driven behaviors. On the other hand, “pull” factors, related to the supply side, refer to the different aspects of sport products the management of sport teams provides. It is imperative to obtain a better understanding of the push–pull interaction so that sport marketers can design their products to satisfy spectators’ expectations with different needs. Spectators (N = 628) attending WNBA games responded to an on-site survey. CFA was conducted to ensure the psychometric properties of the scales, which showed that the overall model fit the data well. A canonical correlation analysis was performed, and two significant functions were revealed by the dimension reduction analysis. The first function [F(40,2,683) = 4.49, p < 0.001]: I-Want-Everything-Consumer suggests that the market segment comprises individuals with multiple needs (ranged from 0.55 to 0.85) and expectations (ranged from 0.55 to 0.89), both of which need to be met simultaneously. Thus, sports marketers can satisfy WNBA consumers’ needs by enhancing the quality of tangible pull factors. The second function [F(28,2,222) = 2.38, p < 0.001]: Achievement-Seekers revealed that the consumers motivated by vicarious achievement (–0.59) expect game promotion (–0.55) rather than the quality of the opposing team (0.42), indicating that sport marketers should provide tailored promotional strategies to satisfy this segment of consumers. Specifically, the findings of this study can be used to segment consumers based upon fan motives (i.e., push factors) and position products accordingly by managing the controllable aspects of sport products (i.e., pull factors). This study provides empirical evidence of the relationship between WNBA consumers’ multiple needs and attributes associated with the WNBA core product.